Public Opinion and Death Penalty Policy Under Direct Democracy Institutions: A Longitudinal Analysis of the American States. Issue 1 (January 2021) - Caron, Christian
Capital punishment remains legal in most U.S. states even though only a small number of them regularly impose it. I attribute the persistence of death penalty statutes to the existence of direct democracy institutions in about half the states. Applying a longitudinal research design that leverages annual estimates of state death penalty opinion, I show that these institutions strengthen the connection between public opinion and capital punishment's legality, indicating that they foster policy responsiveness. By extension, because citizens have generally favored capital punishment, I find that direct democracy states are more likely to have the death penalty. I also demonstrate that direct democracy increases the likelihood that policy will be congruent with majority opinion, especially in states where opinion leans strongly in one direction. The representation-enhancing effect of direct democracy, however, does not extend to the punishment's application, as measured by states' issuance of death sentences.